ANTIMICROBIAL SUSCEPTIBILITY PATTERNS OF PSEUDOMONAS AERUGINOSA ISOLATES FROM BURN WOUNDS - D. B. MANE,; P. R. THORAT,; G. R. PATHADE, (The Bioscan, 2011)
In present study fifty pus samples of burn wound infections were studied for isolation and identification of causative agents. Out of fifty, twenty pus samples showed the presence of Pseudomonas aeruginosa organisms. These 20 isolates were studied for antimicrobial susceptibility against antimicrobial agents like Amoxicillin, Cloxacillin, Erythromycin, Tetracycline, Penicillin, Cotrimoxazole, PenicillinV, Cephalexin, Ciprofloxacin, Ofloxacin, Sparofloxacin, Gatifloxacin, Aztreonam, Azithromycin, Vancomycin, Doxycycline etc. All isolates showed high level of resistance to one or more of above antimicrobials.